Now I'll Tell You Everything - Naylor, Phyllis Reynolds (New York : Atheneum Books for Young Readers, 2013)
As Alice McKinley begins a new phase as a student at the University of Maryland, College Park, she experiences many changes, both expected and surprising, that lead her into a future her seventh-grade self could only have imagined.
Keywords: University of Maryland at College Park -- Juvenile fiction; University of Maryland at College Park -- Fiction; Coming of age -- Juvenile fiction; College students -- Juvenile fiction; Universities and colleges -- Juvenile fiction; Friendship -- Juvenile fiction; Families -- Juvenile fiction -- Maryland; Coming of age -- Fiction; College students -- Fiction; Universities and colleges -- Fiction; Friendship -- Fiction; Family life -- Fiction -- Maryland; Maryland -- Juvenile fiction; Maryland -- Fiction